LUARAN PERDARAHAN INTRAVENTRIKEL YANG DILAKUKAN OPERASI DI DEPARTEMEN BEDAH SARAF RSUPN DR CIPTO MANGUNKUSUMO - Wismaji Sadewo,* Liza Amelia,* Hanif Gordang Tobing,* Setyo Widi Nugroho,* Syaiful Ichwan,* Samsul A (NEURONA, 2017)
INTRODUCTION INTRAVENTRICULAR HEMORRHAGE IVH IS A SPONTANEOUS HEMORRHAGE OCCURRING WITHIN THE VENTRICULAR SYSTEM 3045 OFTEN ASSOCIATED WITH INTRACEREBRAL HEMORRHAGE ICH EVALUATING ACCURATE AND PRECISE DAILY ACTIVITY IN POSTSTROKE PATIENTS IS CRITICAL FOR THE QUALITY OF CARE AND MEASUREMENT OF POSTSTROKE OUTCOMES